Deuterium Metabolic Imaging of the Healthy and Diseased Brain. (15th October 2021) - Straathof, Milou; Meerwaldt, Anu E.; De Feyter, Henk M.; de Graaf, Robin A.; Dijkhuizen, Rick M.
Highlights: DMI is a promising MR spectroscopic imaging method for mapping of active metabolism. DMI enables noninvasive brain mapping of glucose uptake and downstream processing. DMI can detect metabolic disturbances associated with cerebral pathology. Abstract: Altered brain metabolism contributes to pathophysiology in cerebrovascular and neurodegenerative diseases such as stroke and Alzheimer's disease. Current clinical tools to study brain metabolism rely on positron emission tomography (PET) requiring specific hardware and radiotracers, or magnetic resonance spectroscopy (MRS) involving technical complexity. In this review we highlight deuterium metabolic imaging (DMI) as a novel translational technique for assessment of brain metabolism, with examples from brain tumor and stroke studies. DMI is an MRS-based method that enables detection of deuterated substrates, such as glucose, and their metabolic products, such as lactate, glutamate and glutamine. It provides additional detail of downstream metabolites compared to analogous approaches like fluorodeoxyglucose (FDG)-PET, and can be implemented and executed on clinical and preclinical MR systems. We foresee that DMI, with future improvements in spatial and temporal resolutions, holds promise to become a valuable MR imaging (MRI) method for non-invasive mapping of glucose uptake and its downstream metabolites in healthy and diseased brain.